Actors, Structure, and Processes: A Review and Conceptualization of Global Work Integrating IB and HRM Research - Reiche, B. Sebastian; Lee, Yih-teen; Allen, David G. (Journal of management, 2019)
As organizations increasingly fulfill their customer needs by getting their work done globally, there is a pressing need for the scientific community to further advance knowledge on global work, especially in terms of how to better conceptualize and integrate it. A particular opportunity for such development involves the cross-fertilization between the international business (IB) and human resource management (HRM) literatures, which serve as the focal domains to study global work phenomena but have treated global work largely as separate research streams. We therefore edited a special issue to contribute to a more integrative understanding of various aspects of global work across both domains. In this opening article, we review existing research on global work in the multinational enterprise from both IB and HRM perspectives. Subsequently, we present a shared conceptualization of global work that helps integrate theoretical and empirical research in both fields. We then introduce the articles in this special issue, before developing an integrative agenda for future research on global work.